Eksistensi Etika Profesi Keguruan Dalam Menghadapi Krisis Pendidikan Era Society 5.0 - Wagiman Manik; Khadijah Nadhirah Siregar; Zayyan Salsabila; Yuni Maysarah; Annisa Zahrah; Siti Aminah Nasution (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The Society 5.0 era brings significant changes in the world of education, with the integration of technologies such as artificial intelligence and big data. Amidst this progress, challenges such as the dehumanization of learning interactions, inequality in access to technology, and weak implementation of ethical values ​​are issues that must be addressed. This study highlights the existence of professional ethics in teaching as a foundation for dealing with the educational crisis in the Society 5.0 era. Barriers such as lack of understanding of technology and administrative pressure are identified, along with strategies to strengthen professional ethics, such as continuous training and integration of moral values ​​in learning. As a result, this study emphasizes the importance of the role of teachers in creating technology-based education that remains humanistic and ethical.